Mapeando o debate sobre o sistema nacional de educaç\~ao: O que dizem as propostas sobre a criaç\~ao de uma nova instância de pactuaç\~ao - Pedro Arthur de Miranda Marques Pontes; Elaine Cristina Licio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper analyzes recent Legislative propositions regarding the regulation of federative relations in Brazil's education system. These propositions take the form of the National System of Education (Sistema Nacional de Educaç\~ao), which relates to a long-standing reformist tradition. The main focus is the way through which the National System of Education would affect state and municipal autonomy in the governance of education systems. Thus, we describe the main similarities and differences in those law proposals, and demonstrate how they may alter education policy status quo. The main change would be the creation of intergovernmental commissions, transferring decisions today made unilaterally by municipalities, states, and the federal government, to a decision-making body composed by all three components of the Federation.
Keywords: H77; T28; 330; education; education policy; federalism and intergovernmental relations; reform of education systems